2021
DOI: 10.1037/lhb0000458
|View full text |Cite
|
Sign up to set email alerts
|

Pretrial risk assessment validation research: Range restriction and attenuation of predictive validity estimates.

Abstract: Objectives: A growing number of studies have examined the predictive validity of pretrial risk assessments. Overwhelmingly, these validation studies are conducted in the context of routine practice, where not all individuals who are assessed receive pretrial release. Despite evidence of range restriction in pretrial validation research, no study to date has corrected for range restriction in predictive validity estimates. To address this limitation, we examined the effects of range restriction on predictive va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, others have indicated that AUCs less than 0.7 provide poor discrimination (Mandrekar, 2010), suggesting that the threshold used in the field of criminal justice may be somewhat biased in favor of risk assessment tools. 14 Recent research suggests that range restriction, via the detention of a high-risk individuals, may reduce predictive validity estimates (Lowder & Wilson, 2021). Although the share of high-risk defendants detained in the current sample (49%) fell below the threshold of concern identified in this prior work, we nevertheless recognize the potential influence of range restriction on our predictive validity estimates.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…However, others have indicated that AUCs less than 0.7 provide poor discrimination (Mandrekar, 2010), suggesting that the threshold used in the field of criminal justice may be somewhat biased in favor of risk assessment tools. 14 Recent research suggests that range restriction, via the detention of a high-risk individuals, may reduce predictive validity estimates (Lowder & Wilson, 2021). Although the share of high-risk defendants detained in the current sample (49%) fell below the threshold of concern identified in this prior work, we nevertheless recognize the potential influence of range restriction on our predictive validity estimates.…”
Section: Discussionmentioning
confidence: 49%
“…Recent research suggests that range restriction, via the detention of a high‐risk individuals, may reduce predictive validity estimates (Lowder & Wilson, 2021). Although the share of high‐risk defendants detained in the current sample (49%) fell below the threshold of concern identified in this prior work, we nevertheless recognize the potential influence of range restriction on our predictive validity estimates.…”
mentioning
confidence: 99%
“…There have been concerns that this practice results in a restriction of the range of risk scores and therefore affects the predictive validity of risk assessment instruments. However, recent work suggests that more than 40% of people with moderate scores and 60% of people with high-risk scores in a sample must be detained before range restriction meaningfully impacts prediction (Lowder & Wilson, 2021). We are well under this cutoff, given that fewer than 5% of the people in our total sample were detained for the entire pretrial period.…”
Section: Discussionmentioning
confidence: 99%